2009
DOI: 10.1158/1535-7163.mct-09-0191
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin inhibits invasion of prostate cancer PC3 cells through E-cadherin

Abstract: Luteolin, a common dietary flavonoid, has been found to have antitumor properties and therefore poses special interest for the development of preventive and/or therapeutic agent for cancers. E-cadherin, a marker of epithelial cells, mediates cell-cell adhesion. Decreased expression of E-cadherin results in a loss of cell-cell adhesion and an increased cell invasion. Many studies have shown the antiproliferative activities of luteolin on cancer cells. However, the effects of luteolin on invasion of cancer cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 42 publications
2
60
0
Order By: Relevance
“…T persicum extract induced an epithelial-like phenotype in PC-3 cells together with cell membrane localization of E-Cadherin and β-Catenin proteins ( Figure 5 and Figure 6). PC-3 prostate cancer cells have a mesenchymal phenotype and are very invasive and produce tumors in laboratory animals (Zhou et al, 2009;Kandouz et al, 2010;Zhang and Waxman, 2010;Tai et al, 2011). Our results showed that in these cells, both E-Cadherin and β-Catenin proteins were cytoplasmic and cells having either protein at the cell membrane were extremely rare (Figures 5 and 6).…”
Section: Discussionmentioning
confidence: 64%
“…T persicum extract induced an epithelial-like phenotype in PC-3 cells together with cell membrane localization of E-Cadherin and β-Catenin proteins ( Figure 5 and Figure 6). PC-3 prostate cancer cells have a mesenchymal phenotype and are very invasive and produce tumors in laboratory animals (Zhou et al, 2009;Kandouz et al, 2010;Zhang and Waxman, 2010;Tai et al, 2011). Our results showed that in these cells, both E-Cadherin and β-Catenin proteins were cytoplasmic and cells having either protein at the cell membrane were extremely rare (Figures 5 and 6).…”
Section: Discussionmentioning
confidence: 64%
“…Because food derived products exist universally and are expected to be safe, they are highly interesting for development as chemopreventive agents to treat cancer (Sengupta et al, 2002;Chihara et al, 2010). Luteolin act as a strong anticancer agent against many types of malignancies including liver, lung, breast, esophageal squamous carcinoma, colon, prostate and melanoma (Zhou et al, 2009;Hwang et al, 2011;Tang et al, 2011;Wang et al, 2012a;Wang et al, 2012b;Ruan et al, 2012;Pandurangan et al, 2014a). This review is aimed to emphasize the molecular action of luteolin on molecular targets of colorectal cancer.…”
Section: Luteolin a Bioflavonoid Inhibits Colorectal Cancer Through mentioning
confidence: 99%
“…The anticancer effect of Lu also is associated with inducing apoptosis, which involves redox regulation, DNA damage, and protein kinases in inhibiting the proliferation of cancer cells and suppressing metastasis and angiogenesis. 6,[10][11][12][13][14][15][16][17] Moreover, Lu has cytotoxicity in cancer cells or immortalized cells, but not in normal cells, meaning that it has fewer side effects when used in treating cancer. 8,12,18 Yet Lu has some drawbacks, such as poor water solubility (,2 × 10 −2 µmol/mL), 19 low oral absorption, 20 and bioavailability (30.4% in rats), 21 which limit its clinical application.…”
Section: Introductionmentioning
confidence: 99%